Optimization Thickness of Photoanode Layer and Membrane as Electrolyte Trapping Medium for Improvement Dye-Sensitized Solar Cell Performance - Kusumawati, Nita; Setiarso, Pirim; Muslim, Supari; Hafidha, Qonita Arky; Cahyani, Sinta Anjas; Fachrirakarsie, Fadlurachman Faizal (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2024)
Dye-Sensitized Solar Cells (DSSC) are photovoltaic devices that contain a dye that acts as a solar light acceptor. The use of dyesensitized solar cells to solve increasing energy demand and environmental problems still results in low efficiency values. In this study, optimization of DSSC components was carried out to increase DSSC efficiency by varying the thickness of the titanium dioxide (TiO2) semiconductor photoanode layer, polyvinylidene fluoride (PVDF) trap electrolyte membrane, and polyvinylidene fluoride nanofiber (PVDF NF) to obtain the optimum thickness. Scanning Electron Microscope (SEM) results of membrane thickness variation and titanium dioxide (TiO2) semiconductor photoanode coating showed the formation of nanofiber fibers composed of three-dimensional, porous, and diameter networks connected to the PVDF NF membrane. The increase in density and decrease in pore size, along with an increase in thickness and cracking as the TiO2 photoanode semiconductor layer increases, affect the electron transport rate of the DSSC. The higher particle density level will inhibit the electron transport rate, so it can reduce the efficiency of DSSC. The optimum thickness of the TiO2 semiconductor layer and PVDF NF electrolyte membrane of 0.20 mm and 0.35 mm can produce values, voltage, fill factor current density, and electrical efficiency of 500 mV, 2.7 x 10−3 mA.cm−2, 1.80%, and 2.40%, respectively.